Cutaneous hemangiosarcoma in a horse - case report - M.L. Antonioli; P.A. Canola; L.F. Mendonça; P.H.D. Nunes; C.I.S. Oporto; R.O. Vasconcelos (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2024)
ABSTRACT Hemangiosarcoma is a rare neoplasia in horses, with a reported prevalence of 0% to 0.7% and literature reports are few. Here we report a case of cutaneous hemangiosarcoma on the palmaromedial aspect of the metacarpophalangeal joint of the right thoracic limb of a 28-year old mixed breed mare. Macroscopically, the lesion was ulcerated and hemorrhagic, with significant involvement of the surrounding tissues resulting in acquired flexural deformity of the metacarpophalangeal joint and grade 4/5 lameness (AAEP). The diagnosis was confirmed histologically. Surgical ablation was not possible and, in view of the involvement of surrounding tissues and the age of the patient, the lesion was treated conservatively.